Strategi Pengelolaan Obyek Wisata Tane’ Olen yang Berkelanjutan di Desa Wisata Setulang, Kecamatan Malinau Selatan Hilir Kabupaten Malinau - Setiono, Yuhar; Susanto, Agus; Hamzah, A. Hadian Pratama (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to develop strategy input for developing the potential economic value of environmental services at the Tane'Olen Tourism Object using the TCM (Travel Cost Method) method approach. The research was conducted using a combined research approach model between quantitative research and qualitative research. The data collected was processed quantitatively and described qualitatively (The Explanatory Sequential Design). The results of the research show that the programs that are necessary in the sustainable management of the Tane'Olen Object are meeting the needs of: promotion of arts and culture, adequate infrastructure, maintained environmental quality, development of community empowerment, sustainable conservation of the Tane'olen forest, preservation of local wisdom, improvement Setulang Village PAD and improving community welfare, all elements of these needs are in quadrant III; These 8 (eight) sub-elements of needs are the basis for managing the Tane'Olen Object.